A Novel Description of the Human Sinus Archaeome During Health and Chronic Rhinosinusitis - Wagner Mackenzie, Brett; West, Annie G.; Waite, David W.; Lux, Christian A.; Douglas, Richard G.; Taylor, Michael W.; Biswas, Kristi (Frontiers in Cellular and Infection Microbiology, 2020)
Human microbiome studies remain focused on bacteria, as they comprise the dominant component of the microbiota. Recent advances in sequencing technology and optimization of amplicon sequencing protocols have allowed the description of other members of the microbiome, including eukaryotes (fungi) and, most recently, archaea. There are no known human-associated archaeal pathogens. Their diversity and contribution to health and chronic respiratory diseases, such as chronic rhinosinusitis (CRS), are unknown. Patients with CRS suffer from long-term sinus infections, and while the microbiota is hypothesized to play a role in its pathogenesis, the exact mechanism is poorly understood. In this cross-sectional study, we applied a recently optimized protocol to describe the prevalence, diversity and abundance of archaea in swab samples from the middle meatus of 60 individuals with and without CRS. A nested PCR approach was used to amplify the archaeal 16S rRNA gene for sequencing, and bacterial and archaeal load (also based on 16S rRNA genes) were estimated using Droplet Digital™ PCR (ddPCR). A total of 16 archaeal amplicon sequence variants (ASVs) from the phyla Euryarchaeota and Thaumarchaeota were identified. Archaeal ASVs were detected in 7/60 individuals, independent of disease state, whereas bacterial ASVs were detected in 60/60. Bacteria were also significantly more abundant than archaea. The ddPCR method was more sensitive than amplicon sequencing at detecting archaeal DNA in samples. Phylogenetic trees were constructed to visualize the evolutionary relationships between archaeal ASVs, isolates and clones. ASVs were placed into phylogenetic clades containing an apparent paucity of human-associated reference sequences, revealing how little studied the human archaeome is. This is the largest study to date to examine the human respiratory-associated archaeome, and provides the first insights into the prevalence, diversity and abundance of archaea in the human sinuses.